Flame characteristics of a high-pressure LOX/H2 rocket combustor with large optical access. (December 2021) - Martin, Jan; Armbruster, Wolfgang; Stützer, Robert; General, Stephan; Knapp, Bernhard; Suslov, Dmitry; Hardi, Justin
Abstract: Hot fire tests were performed with a newly developed single-injector research combustor featuring a large optical access (255 × 38 mm) for flame imaging. Within these tests the propellant combination of liquid oxygen and cold gaseous hydrogen (LOX/H2 ) has been used at chamber pressures up to 70 bar and ratios of oxidizer to fuel (ROF) at the main injector of 3.4–6. The large optical access enabled synchronized flame imaging using OH* and blue radiation wavelengths covering an area of the combustion chamber from the injection plane to shortly before the contraction section of the nozzle. High-speed flame imaging was realized for three different operating conditions. Combined with data from temperature, pressure and unsteady pressure sensors high-quality validation data for numerical modeling has been gained. Several key dimensions of the flame topology were extracted from the imaging. The change in flame topology in response to different operating conditions is consistent with expectations from the literature, in particular the dependence of flame opening angle on injection momentum flux ratio. Using OH* imaging for such topology measurements was found to have less uncertainty than with blue radiation imaging.